Generic structure analysis of acknowledgements in undergraduate academic exercises / Marina Muhammad - Muhammad, Marina (2012)
Acknowledgements are common to academic writing. They are well known as a page of gratitude for assistance, expressed by the writers to those who have supported them in any way. However, the importance of acknowledgements in academic writing seems to be ignored and given less attention (Hyland, 2004, and Al-Ali, 2006). Therefore, this study is carried out in order to analyse the generic structure of acknowledgements. Also, previous studies on the same genre are also reviewed to share the importance of acknowledgements and its implications for genre analysis. For this study, 50 texts were selected from undergraduate academic exercises from the Faculty of Education, UiTM Section 17, Shah Alam, Selangor. The Three-Tier structure proposed in Hyland (2004), modified in Al-Ali (2006) was used. The results revealed that only the second tier (Move 2) was included in most of the texts. The first and third tiers, (Move 1 and Move 3) were apparently not popular. The results were found to be similar to previous studies of the same genre by Hyland (2004), Al-Ali (2006), and Mingwei and Yajun (2010). Also, the findings might help students to improve their academic writings in future. This study also offers some recommendations for future studies on the same genres.